Traveling across Racial Borders: TripAdvisor and the Discursive Strategies Businesses Use to Deny Racism. Issue 4 (October 2019) - Dalmage, Heather M.
Travel and leisure activities can bring many rewards, and yet for those deemed "racialized Others, " these same activities can be fraught with anxiety and tension. As in all aspects of society, racism mediates the rewards of travel and leisure. Decisions about when and how to confront racism are central in the lives of those considered racialized Others. Given a wish to de-escalate racist situations and respond later, some individuals are using online platforms to call out racism. Using a digital discourse analysis, the author explores TripAdvisor, as a site and context in which racial confrontation happens. Interracial couples facing discrimination during leisure activities may choose to confront businesses after the fact through an online platform. When businesses respond, they follow a pattern that defensively separates "service" from racism and ultimately denies racism entirely. The author begins with an analysis of the TripAdvisor platform, including the affordances and constraints. Next, the author uses a digital discourse analysis of the review-response interaction. As with other forms of colorblind racism, a close read of the content is needed to highlight racist practices. The author shows that the structure of TripAdvisor, including the quantitative ratings and rankings and written reviews and responses, works to legitimize the platform and build trust across a Eurocentric global community. This sense of community and trust is denied and remains elusive to those suffering as a result of racist abuse.